Winds of change : the environmental movement and the global development of the wind energy industry - Vasi, Ion Bogdan (Oxford ; New York : Oxford University Press, 2011)
In Winds of Change, Ion Bogdan Vasi argues that the development of wind energy is dependent not only on improvements in technology and economic forces, but also in large part on the efforts of the environmental movement. Vasi defines and analyzes three pathways through which the environmental movement has contributed to industry growth: it has influenced the adoption and implementation of renewable energy policies, created consumer demand for clean energy, and changed the institutional logics of the energy sector. Vasi uses quantitative analysis to present the big picture of global wind power development, and qualitative research to understand why certain countries are world leaders in wind energy while others are relatively underdeveloped. Through interviews with renewable energy professionals and campaigners, he shows that environmental groups and activists participated actively in energy policymaking, pressured various organizations to purchase wind power, and formed new companies that specialized in wind-farm development. He also demonstrates that environmentalists contributed to wind turbine manufacturing by becoming entrepreneurs, innovators, and advocates. --Book Jacket
The wind energy industry and the environmental movement -- The big picture: The environmental movement's impact on the global development of the wind energy industry -- Environmental campaigns and the adoption and implementation of feed-in tariffs -- Environmental campaigns and the adoption and implementation of renewable portfolio standards -- From thinking globally about climate change to acting locally on the energy challenge -- Going with the wind: the environmentalist transformation of the electricity sector -- The answer may be blowing in the wind
Includes bibliographical references (235-249) and index
Keywords: Wind power industry; Environmentalism